Potensi dan Daya Tarik Wisata Kuliner Bolu Meranti untuk Pengembangan Pariwisata di Kota Medan - Angelia Putriana; Jayanti Pratiwi (Yayasan Literasi Sains Indonesia, 2022)
Potential must be applied in any business (business). In the culinary world of course also has potential. It can be seen from Meranti's fried sponge cake, started by an ordinary housewife who has a hobby of making cakes so that her family and even her neighbors like it, and eventually turned into a small business which was flooded with orders from her neighbors. This study uses a qualitative descriptive research methodology by conducting interviews with shop owners and customers. The results of this research in the end Meranti sponge rolls developed rapidly and even became one of the typical souvenirs of the city of Medan. Product attractiveness is everything that a trader/seller can offer to be noticed, requested, sought, purchased, consumed by the market as a fulfillment of the needs or desires of the relevant market. Emphasizes the characteristics of the emerging product category that will lead to the evaluation of potential customers in the category. If the characteristics become more attractive to all customers, the more attractive the product category is to them, increasing the likelihood that customers will adopt the update and make a purchase. The potential and attractiveness of Meranti Sponge Rolls already exists and has been very good because the manager maintains the product quality and service quality of Meranti Sponges to date and can maintain this business and can even open several branches to date, therefore Meranti Sponges are often a souvenir.